Wykorzystanie controllingu w zakładach energetycznych - Rubik, Jolanta (The Use of Controllership in Energetics Companies, 2006)
The paper presents the results of questionnaire on „controllership in energetics companies". Researches focused on organizational, toolkit and informative aspects of controllership. The aim of questionnaire was to fix the level of controllership improvement in Polish energetics companies. It can be a support in establishing conditions of controllership improvement in the future.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1139, s. 360-370